Comparison of Effect between Inhalative Anesthetics with Isoflurane and Sevoflurane on Oxygen Saturation - Prabuwinoto Setiawan; M.H. Sudjito; Ari Probandari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Inhalative anesthesia with isoflurane and sevoflurane are known to lower the oxygen saturation in patients. Both of these agents reduce the ventilation response to hypoxia. The aim of this study was to compare the effect of giving inhaled anesthetics isoflurane and sevoflurane to changes in oxygen saturation. Methods: This study was an observational analytic study with cross-sectional approach. The study was conducted at the Central Installation of Surgery dr. Moewardi Hospital. Samples were taken by consecutive sampling. There were two groups in this study, the first group received isoflurane anesthesia, the other group received sevoflurane anesthesia. Changing of oxygen saturation during operation was observed for two groups used bedside monitor. The data which have been collected analyzed using the Mann Whitney test and Pearson correlation test. Results: This study revealed a decrease in oxygen saturation for both groups in the induction phase (sevoflurane = 97.42 0.90; isoflurane = 97.00 0.75; p = 0.113). However, the oxygen saturation of isoflurane group was more fluctuating than sevoflurane group after inducton phase (p intubation = 0.001; p incision 5 = 0.117; p incision 10 = 0.001; p incision 15 = 0.048). The further analysis showed no statistically significant difference in oxygen saturation between the isoflurane and the sevoflurane groups (p = 0.113). Conclusions: There are no significant differences in changing of oxygen saturation between the isoflurane and sevoflurane anesthesia on the induction phase, 5 minutes and 15 minutes after incision. Anesthesia with sevoflurane in oxygen saturation is more stable compared with isoflurane anesthesia on intubation phase until 15 minutes after incision. Keywords: inhalation anesthesia, sevoflurane, isoflurane, hemodynamic, oxygen saturation